Peningkatan Kreatifitas Bercerita Bahasa Indonesia Melalui Media Kartu Kata Pada Siswa Kelas 1 SD Negeri Kebonturi Kecamatan Jaken Kabupaten Pati Tahun Pelajaran 2014/2015 - Rukin, Rukin; , Drs. M. Yahya, M.Si (2015)
This study aimed to describe the increase in creativity Indonesian storytelling through the use of media cards word I said in class Elementary School Kebonturi 2014/2015 school year. This research is qualitative research and design research is a class act that consists of 2 cycles. The first cycle through the media card without a picture and said second cycle using the word media card with pictures. This study was conducted in primary school Kebonturi, with first grade students study subjects with the number of 14 students, consisting of 6 girls and 8 boys and the object of this research is telling Indonesian creative and media use the word cards. Data collection techniques by means of interviews, observation (observation), documentation, and field notes. The data analysis technique that is descriptive and percentage kualitatif.dengan pensekoran way. Research shows creativity Indonesian storytelling cycle I gained an average score of 16.8 in both categories and cycle II receives an average score of 20.3 with a very good category. Creativity percentage of students in the first cycle is 67.2% and in the second cycle percentage 81.2%. Data resulting from the use of said media card in the first cycle to obtain an average score of 37 in both categories and cycle II receives an average score of 45 with very good category. Percentage of media use the word cards in the first cycle and 74% in the second cycle percentage is 90%. Cycle I thoroughness percentage 64% or 9 students who completed the second cycle and thoroughness to 86% or 12 students who completed. Based on the study concluded that the creative storytelling Elementary School first grade students of the school year 2014/2015 in Kebonturi Indonesian lessons can be enhanced through the media and media use the word cards word cards can improve both the learning activities of prakegiatan, initial activities, core, and the final activity or so that the cover can be used as an alternative solution to improve learning Indonesian in SD